2001
DOI: 10.1054/bjoc.2001.1995
|View full text |Cite
|
Sign up to set email alerts
|

Tumour markers in breast carcinoma correlate with grade rather than with invasiveness

Abstract: Summary Ductal breast carcinoma in situ (DCIS) is regarded as a precursor to invasive breast cancer. The progression from in situ to invasive cancer is however little understood. We compared some tumour markers in invasive and in situ breast carcinomas trying to find steps in this progression. We designed a semi-experimental setting and compared histopathological grading and tumour marker expression in pure DCIS (n = 194), small invasive lesions (n = 127) and lesions with both an invasive and in situ component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
2
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 19 publications
10
68
2
2
Order By: Relevance
“…Our results are also in agreement with other molecular studies on cancer proliferation, biology, and genetics, which demonstrated that lobular tumors exhibited similarities to low-grade ductal tumors [22][23][24]. Several studies have revealed a striking similarity between in situ and invasive breast cancers, where all markers correlated with grade rather than with tumor invasiveness [22,[25][26][27], and there was a good concordance between grade in primary and metastatic tumors [28][29][30]. Recent molecular studies have demonstrated that qualitative and quantitative differences exist between ER(?)…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also in agreement with other molecular studies on cancer proliferation, biology, and genetics, which demonstrated that lobular tumors exhibited similarities to low-grade ductal tumors [22][23][24]. Several studies have revealed a striking similarity between in situ and invasive breast cancers, where all markers correlated with grade rather than with tumor invasiveness [22,[25][26][27], and there was a good concordance between grade in primary and metastatic tumors [28][29][30]. Recent molecular studies have demonstrated that qualitative and quantitative differences exist between ER(?)…”
Section: Discussionsupporting
confidence: 92%
“…2 and 3). This finding is consistent with a previous study indicating that expression of several prominent tumor markers (p53, ERBB2, Ki-67, ER, PR, and bcl2) correlate with tumor grade but not with the distinction between DCIS and IDC (17). Nonetheless, it is of great interest to understand the transcriptional program that drives invasive growth due to its clinical importance.…”
Section: Gene Expression Profiles Of Breast Tumor Gradessupporting
confidence: 92%
“…All DCIS tumours in the present study were previously analysed as part of a study assessing the status of p53, c-erbB-2, Ki-67, ER, PR, Bcl-2, and angiogenesis in DCIS and invasive carcinomas (see Table II) [28]. These markers correlated with grade as the DCIS grade 3 tumours had a more malignant pattern for all of them.…”
Section: Discussionmentioning
confidence: 85%
“…The samples were previously analysed by immunohistochemical staining of p53, c-erbB-2, Ki-67, Bcl-2, and the hormone-receptors for oestrogen and progesterone (results shown in Table I) [28]. New slides, 15 Á/17 mm thick, were cut from the paraffin blocks and stained with toluidine blue.…”
Section: Microdissection and Dna Extractionmentioning
confidence: 99%